Composite fire-resistant prefabricated brick for artificially synthesized mica smelting furnace and preparation method of composite fire-resistant prefabricated brick
By using composite refractory prefabricated bricks made of zirconium corundum, white corundum and other materials in artificial synthetic mica furnaces, the overall structure is formed using bridging agents, which solves the problems of corrosion and pollution of refractory lining materials, and improves product yield and furnace service life. Reduced resource waste and environmental pollution.
Patent Information
- Application Number
- CN202411345567.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The refractory lining materials of existing synthetic mica furnaces are prone to erosion, adhesion and pollution at high temperatures, and are difficult to separate products, resulting in waste of resources and environmental pollution, and strict control of impurities, affecting product yields.
Composite refractory prefabricated bricks made of zirconium corundum, white corundum, alumina and other materials are used to form an overall structure through bridge agent A and bridge agent B to improve corrosion resistance and avoid adhesion of lining materials with products, ensuring separation and cleanliness.
It realizes an overall structure that is resistant to high temperature and corrosion, reduces impurities content, improves product yield, extends the service life of the furnace, and reduces resource waste and environmental pollution.
Smart Images

Figure CN119191824A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a material for an artificial synthetic mica furnace, in particular to a composite refractory prefabricated brick for an artificial synthetic mica furnace and a preparation method thereof, belonging to the technical field of artificial synthetic mica production equipment. Background Art
[0002] Mica has excellent elasticity, transparency, high-frequency insulation and chemical stability, and is widely used in aerospace, electrical appliances, paints, cosmetics and other fields. At present, high-quality natural mica resources are mainly concentrated in a few countries such as India, Canada, and Brazil, while my country's high-quality natural mica resources are relatively scarce. Therefore, artificial synthetic mica came into being. Artificial synthetic mica is also called fluorphlogopite (KMg3 (AlSi3O 10 )F2), is a typical layered silicate. It is a natural mica (general formula X 0.5-1 Y 2-3 Z 10 OH in (OH)2 - Adopt F - This synthetic mica can withstand high temperatures above 1200°C, has a higher resistivity (about 1000 times higher) than natural mica, is more acid-resistant and alkali-resistant, can be peeled, is transparent and elastic. Therefore, synthetic mica has a wider range of applications.
[0003] The main processes for synthetic mica are the internal heating method and the crucible descending seed method. The crucible descending seed method uses platinum crucible smelting, which is costly and cannot be adapted to large-scale production. The internal heating method uses a refractory lining as the furnace pool wall, places the raw materials in a certain proportion in the furnace, and melts the materials by electrode heating. After cooling, the synthetic mica products are obtained. Although the internal heating method can produce mica products on a large scale, the refractory lining is severely corroded during the smelting process due to the presence of fluoride, potassium, and sodium in the synthetic mica products, and the lining material adheres to the mica products, making it extremely difficult to remove, and causing a certain degree of pollution to the mica products.
[0004] In the prior art, the production of synthetic mica usually adopts an integrated furnace (furnace). The refractory bricks used in the lining materials of the smelting furnace for synthesizing synthetic mica are basically disposable products. New lining materials need to be replaced for each furnace, resulting in great waste and environmental pollution. In addition, the product separation process is difficult to carry out when the integrated structure of the furnace is used for production, and there are problems such as kiln caking and product pollution. CN111829344A proposes a prefabricated brick structure, which is convenient for the disassembly and assembly of the furnace in the process of synthetic mica, but the problems of kiln caking, corrosion, and product pollution still exist. CN 218380427 U discloses an electric heating melting homogenization furnace, whose refractory lining adopts a double-layer structure, but it is used for the production of synthetic mica, and its high temperature resistance and corrosion resistance are poor, and there is also a technical problem of double-layer structure detachment. In order to solve the separation problem of synthetic mica products, CN109813113A discloses a circulating kiln for producing synthetic mica, i.e., a mica production method, in which an inert barrier layer is arranged on the inner surface of the cylindrical furnace body, and the material of the inert barrier layer is a metal element or a metal alloy with a melting point greater than 1750°C. However, the material of the inert barrier layer is completely different from that of the kiln lining. During the cooling process of the kiln, the thermal expansion coefficients of the inert barrier layer and the kiln lining are completely different, resulting in a technical problem of separation of the two layers. CN116144204A discloses a separation coating for an artificial synthetic mica smelting furnace, wherein the separation coating for an artificial synthetic mica smelting furnace is coated on the refractory bricks of the artificial synthetic mica smelting furnace; a layer of separation coating is applied on the working surface of the refractory bricks, and the separation coating has excellent anti-corrosion performance against mica solution; then, the difference in thermal expansion coefficients between the separation coating and the refractory bricks is utilized to automatically separate the synthetic mica melt from the refractory bricks after cooling; that is, after separation, the separation coating and the artificial synthetic mica are integrated into one, and are separated from the refractory bricks together, which results in a technical problem of contaminating the artificial synthetic mica product.
[0005] In the existing technology, the use of furnace-synthesized artificial mica has the problem of product separation difficulties and easy detachment of the isolation layer; the furnace lining material contaminates the synthetic mica product, and the control of impurity elements in artificial synthetic mica is extremely strict, with a control range of less than one thousandth, and the contaminated mica product can only be discarded, which reduces the product yield. In summary, the refractory lining material of the smelting furnace has seriously restricted the technological development of the artificial synthetic mica industry. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention proposes a high-temperature resistant and erosion-resistant refractory prefabricated block, which includes a working surface and a backing surface. The working surface utilizes small-sized grains and a unique dendritic eutectic structure formed by white corundum, zirconium oxide or synthetic zirconium corundum under high temperature conditions to achieve corrosion resistance; a bridging agent A is added to the raw material of the working surface, and a bridging agent B is added to the raw material of the backing surface. Through the action of the bridging agent A and the bridging agent B, the working surface and the backing surface form a complete integrated structure, thereby avoiding the falling off of the working surface, and then avoiding pollution to the product, further reducing impurities in artificial synthetic mica, and improving the yield of the product.
[0007] According to a first embodiment provided by the present invention, a composite refractory prefabricated brick for an artificial synthetic mica furnace is provided.
[0008] A composite refractory prefabricated brick for an artificial synthetic mica melting furnace, the composite refractory prefabricated brick comprising a working surface and a backing surface. The working surface raw material is composed of one or more of zirconium corundum powder, white corundum powder, and alumina powder, a thickener, and a bridging agent A. The backing surface raw material is composed of coke powder and / or high-alumina bauxite powder as aggregate, and one or more of white corundum powder, calcium aluminate cement, coke powder, and alumina powder, an additive, and a bridging agent B as fine powder.
[0009] Wherein: bridging agent A is one or more of sodium carbonate, sodium silicate, potassium carbonate and potassium silicate; bridging agent B is sodium disilicate and / or phosphorus pentoxide.
[0010] Preferably, the bridging agent A is sodium silicate, and the bridging agent B is phosphorus pentoxide.
[0011] In the present invention, the amount of bridging agent A in the working surface raw materials is 0.01-1wt%, preferably 0.05-0.8wt%, more preferably 0.1-0.5wt% and further preferably 0.15-0.4wt% of the total amount of other raw materials of the working surface. For example: 0.1wt%, 0.12wt%, 0.15wt%, 0.18wt%, 0.2wt%, 0.22wt%, 0.25wt%, 0.26wt%, 0.28wt%, 0.3wt%, 0.32wt%, 0.35wt%, 0.38wt%, 0.4wt%, 0.42wt%, 0.45wt%, 0.48wt%, 0.5wt%.
[0012] In the present invention, the amount of bridging agent B in the backing surface raw material is 0.01-1wt%, preferably 0.05-0.8wt%, more preferably 0.1-0.5wt% and further preferably 0.15-0.4wt% of the total amount of other raw materials of the backing surface. For example: 0.1wt%, 0.12wt%, 0.15wt%, 0.18wt%, 0.2wt%, 0.22wt%, 0.25wt%, 0.26wt%, 0.28wt%, 0.3wt%, 0.32wt%, 0.35wt%, 0.38wt%, 0.4wt%, 0.42wt%, 0.45wt%, 0.48wt%, 0.5wt%.
[0013] As a preferred embodiment, the raw material composition of the working surface is: The zirconium corundum powder is 70-90 parts by weight, preferably 72-88 parts by weight, and more preferably 74-86 parts by weight; for example: 70 parts by weight, 72 parts by weight, 74 parts by weight, 75 parts by weight, 76 parts by weight, 78 parts by weight, 80 parts by weight, 81 parts by weight, 82 parts by weight, 83 parts by weight, 85 parts by weight, 86 parts by weight, 88 parts by weight, and 90 parts by weight.
[0014] 2-30 parts by weight of white corundum powder, preferably 4-25 parts by weight, more preferably 6-20 parts by weight; for example: 2 parts by weight, 4 parts by weight, 6 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.5 parts by weight, 10 parts by weight, 10.2 parts by weight, 10.5 parts by weight, 10.6 parts by weight, 10.8 parts by weight, 11 parts by weight, 11.5 parts by weight, 12 parts by weight, 12.5 parts by weight, 13 parts by weight, 13.5 parts by weight, 14 parts by weight, 14.5 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight.
[0015] The amount of alumina powder is 2-30 parts by weight, preferably 4-25 parts by weight, and more preferably 6-20 parts by weight; for example: 2 parts by weight, 4 parts by weight, 6 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.5 parts by weight, 10 parts by weight, 10.2 parts by weight, 10.5 parts by weight, 10.6 parts by weight, 10.8 parts by weight, 11 parts by weight, 11.5 parts by weight, 12 parts by weight, 12.5 parts by weight, 13 parts by weight, 13.5 parts by weight, 14 parts by weight, 14.5 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, and 20 parts by weight.
[0016] The thickener is 0.1-2 parts by weight, preferably 0.15-1.5 parts by weight, and more preferably 0.2-1 parts by weight; for example: 0.1 parts by weight, 0.15 parts by weight, 0.16 parts by weight, 0.18 parts by weight, 0.2 parts by weight, 0.22 parts by weight, 0.25 parts by weight, 0.28 parts by weight, 0.3 parts by weight, 0.32 parts by weight, 0.35 parts by weight, 0.38 parts by weight, 0.4 parts by weight, 0.42 parts by weight, 0.45 parts by weight, 0.48 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight, 1.0 parts by weight, 1.1 parts by weight, 1.2 parts by weight, 1.3 parts by weight, 1.4 parts by weight, 1.5 parts by weight.
[0017] Bridging agent A 0.01-1 weight part, preferably 0.05-0.8 weight part, more preferably 0.1-0.5 weight part; for example: 0.01 weight part, 0.05 weight part, 0.08 weight part, 0.1 weight part, 0.12 weight part, 0.15 weight part, 0.18 weight part, 0.2 weight part, 0.22 weight part, 0.25 weight part, 0.28 weight part, 0.3 weight part, 0.32 weight part, 0.35 weight part, 0.38 weight part, 0.4 weight part, 0.45 weight part, 0.5 weight part, 0.6 weight part, 0.7 weight part, 0.8 weight part, 0.9 weight part, 1.0 weight part.
[0018] Preferably, the raw material of the backing surface includes aggregate raw material and fine powder raw material.
[0019] The amount of aggregate is 50-90% of the total amount of the backing surface, preferably 55-85%, more preferably 60-80%, and further preferably 65-75%. For example, 60%, 62%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 82%, 85%, 88%, 90%.
[0020] Preferably, the raw materials of the aggregate are all composed of high-alumina bauxite powder, or are all composed of coke powder, or are a mixture of high-alumina bauxite powder and coke powder in any proportion. For example: the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:0.1, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:0.2, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:0.3, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:0.4, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:0.5, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:0.6, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:0.7, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:0.8, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:0.9, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1:1, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1.1, the raw material of aggregate is composed of high alumina bauxite powder and pyrojewel powder in a ratio of 1.2 The raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:1.3, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:1.5, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:1.8, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:2, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:3, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:4, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:5, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:6, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:7, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:8, the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:9, and the raw materials of aggregate are composed of high alumina powder and pyrojewel powder in the ratio of 1:10.
[0021] Preferably, the raw material composition of the fine powder is: 2-25 parts by weight of white corundum powder, preferably 4-20 parts by weight, more preferably 6-15 parts by weight; for example: 2 parts by weight, 4 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.2 parts by weight, 9.5 parts by weight, 9.8 parts by weight, 10 parts by weight, 10.2 parts by weight, 10.5 parts by weight, 10.6 parts by weight, 10.8 parts by weight, 11 parts by weight, 11.2 parts by weight, 11.5 parts by weight, 11.8 parts by weight, 12 parts by weight, 12.5 parts by weight, 13 parts by weight, 13.5 parts by weight, 14 parts by weight, 14.5 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight.
[0022] The coke gem powder is 5-25 parts by weight, preferably 7-20 parts by weight, and more preferably 10-15 parts by weight; for example: 2 parts by weight, 4 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.2 parts by weight, 9.5 parts by weight, 9.8 parts by weight, 10 parts by weight, 10.2 parts by weight, 10.5 parts by weight, 10.6 parts by weight, 10.8 parts by weight, 11 parts by weight, 11.2 parts by weight, 11.5 parts by weight, 11.8 parts by weight, 12 parts by weight, 12.2 parts by weight, 12.5 parts by weight, 12.8 parts by weight, 13 parts by weight, 13.5 parts by weight, 14 parts by weight, 14.5 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, and 20 parts by weight.
[0023] The amount of alumina powder is 1-10 parts by weight, preferably 2-9 parts by weight, and more preferably 3-8 parts by weight; for example: 2 parts by weight, 3 parts by weight, 4 parts by weight, 4.2 parts by weight, 4.5 parts by weight, 4.8 parts by weight, 5 parts by weight, 5.2 parts by weight, 5.5 parts by weight, 5.8 parts by weight, 6 parts by weight, 6.2 parts by weight, 6.5 parts by weight, 6.8 parts by weight, 7 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.2 parts by weight, 9.5 parts by weight, 9.8 parts by weight, and 10 parts by weight.
[0024] 1-10 parts by weight of calcium aluminate cement, preferably 2-9 parts by weight, more preferably 3-8 parts by weight; for example: 2 parts by weight, 3 parts by weight, 4 parts by weight, 4.2 parts by weight, 4.5 parts by weight, 4.8 parts by weight, 5 parts by weight, 5.2 parts by weight, 5.5 parts by weight, 5.8 parts by weight, 6 parts by weight, 6.2 parts by weight, 6.5 parts by weight, 6.8 parts by weight, 7 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.2 parts by weight, 9.5 parts by weight, 9.8 parts by weight, 10 parts by weight.
[0025] The additive is 0.5-10 parts by weight, preferably 1-8 parts by weight, and more preferably 2-5 parts by weight; 1 part by weight, 1.2 parts by weight, 1.5 parts by weight, 2 parts by weight, 2.2 parts by weight, 2.5 parts by weight, 2.8 parts by weight, 3 parts by weight, 3.2 parts by weight, 3.5 parts by weight, 3.8 parts by weight, 4 parts by weight, 4.2 parts by weight, 4.5 parts by weight, 4.8 parts by weight, 5 parts by weight, 5.5 parts by weight, 6 parts by weight, 6.5 parts by weight, 7 parts by weight, 7.5 parts by weight, and 8 parts by weight.
[0026] Bridging agent B 0.01-1 weight part, preferably 0.05-0.8 weight part, more preferably 0.1-0.5 weight part; for example: 0.01 weight part, 0.05 weight part, 0.08 weight part, 0.1 weight part, 0.12 weight part, 0.15 weight part, 0.18 weight part, 0.2 weight part, 0.22 weight part, 0.25 weight part, 0.28 weight part, 0.3 weight part, 0.32 weight part, 0.35 weight part, 0.38 weight part, 0.4 weight part, 0.45 weight part, 0.5 weight part, 0.6 weight part, 0.7 weight part, 0.8 weight part, 0.9 weight part, 1.0 weight part.
[0027] In the present invention, the particle size of the zirconium corundum powder is ≤0.076 mm, the Al2O3 content is ≥65%, the ZrO2 content is ≥20%, and the SiO2 content is ≤15%.
[0028] In the present invention, the particle size of the white corundum powder is ≤0.076 mm, and the Al2O3 content is ≥99%.
[0029] In the present invention, the Al2O3 in the alumina powder is ≥99 and the particle size is 0.5-10 μm.
[0030] In the present invention, Al2O3 in the high-alumina bauxite is ≥ 65%.
[0031] In the present invention, the Al2O3 content in the coke gemstone powder is 30-50%, and the Fe2O3 is ≤2%.
[0032] In the present invention, the thickener is hydroxymethyl cellulose or polyacrylamide.
[0033] In the present invention, the additive is one or more of silica fume, sodium tripolyphosphate or sodium hexametaphosphate.
[0034] Preferably, in the backing surface aggregate raw materials, the pyrope stone powder is composed of pyrope stone powder of various particle sizes.
[0035] Preferably, in the backing surface aggregate raw material, high alumina powder is composed of high alumina powder of various particle sizes.
[0036] Preferably, the backing surface aggregate raw materials include raw materials with particle sizes of 0.5-1mm, 1-2mm, 2-3mm, and 3-5mm; preferably, the raw materials with a particle size of 0.5-1mm account for 20-30%, the raw materials with a particle size of 1-2mm account for 15-25%, the raw materials with a particle size of 2-3mm account for 15-25%, and the raw materials with a particle size of 3-5mm account for 20-30%.
[0037] Preferably, the calcium aluminate cement is pure calcium aluminate cement, with Al2O3 72-82% and CaO 19-23%.
[0038] Preferably, the alumina powder is activated alumina powder.
[0039] In the present invention, the thickness of the working surface is 5-50 mm, preferably 8-30 mm, and more preferably 10-20 mm.
[0040] In the present invention, the thickness of the backing surface is 100-500 mm, preferably 150-400 mm, and more preferably 200-300 mm.
[0041] According to a second embodiment provided by the present invention, a method for preparing composite refractory precast bricks for artificial synthetic mica melting furnaces or a method for preparing the composite refractory precast bricks for artificial synthetic mica melting furnaces described in the first embodiment is provided.
[0042] A method for preparing composite refractory prefabricated bricks for artificial synthetic mica furnace, the method comprising the following steps: (1) Preparation of backing surface mud: add the backing surface fine powder raw material in proportion and mix evenly to obtain matrix fine powder; then mix the backing surface aggregate evenly, add the matrix fine powder, and then add 1-10% of water and mix to obtain backing surface mud; (2) Preparation of working surface mud: Add the working surface raw materials according to proportion, mix evenly, add 15-25% of water, continue stirring, and obtain the working surface mud; (3) Preparation of composite refractory precast bricks for artificial synthetic mica melting furnace: first, pour the backing surface mud into the mold and vibrate to form it. After the backing surface mud is vibrated to level it, pour the working surface mud into the mold and vibrate to form it. After vibrating and solidifying, the composite refractory precast bricks for artificial synthetic mica melting furnace are obtained.
[0043] In the present invention, the stirring and mixing are performed using a stirrer.
[0044] In the present invention, the material of the mold is not limited, and can be any one of wood, iron, steel, alloy, etc. The shape of the mold is not limited, and the interface of the mold can be any one of square, rectangle, arc, circle, sector, wedge, triangle, rhombus, etc.
[0045] In the present invention, the vibration is performed by a vibration machine or a vibration rod.
[0046] In the present invention, the solidification includes drying, baking, roasting or sintering.
[0047] In view of the existing technology, the manufacture of artificial synthetic mica is carried out in a kiln (or a melting furnace), which has technical problems such as raw materials corroding the kiln lining (or lining), the lining material entering the product, the kiln lining detaching, and the kiln lining delamination. The present invention provides an integrated composite refractory prefabricated brick for a synthetic mica melting furnace. The composite refractory prefabricated brick provided by the present invention is an integral structure, including a working surface and a backing surface. The working surface and the backing surface are an integrated structure. When a melting furnace made of the composite refractory prefabricated brick is used to produce artificial synthetic mica, the working surface and the backing surface are always an integral structure, and will not separate or fall off. Therefore, there is no problem of lining material entering the product. The working surface achieves corrosion resistance through small-sized grains and a unique dendritic eutectic structure formed by white corundum, zirconium oxide or synthetic zirconium corundum under high temperature conditions.
[0048] In the present invention, the working surface adopts one or more of zirconium corundum powder, white corundum powder, alumina powder and thickener and bridging agent A as raw materials. The formed working surface is resistant to high temperature and corrosion, which avoids or reduces the corrosion of artificial synthetic mica raw materials to the working surface, and also avoids the constituent materials of the working surface from entering the product.
[0049] In the present invention, the backing made of the backing surface raw material plays a supporting role, and uses high-temperature resistant and thermally insulating pyrope stone powder and / or high-alumina bauxite powder as aggregate, and one or more of white corundum powder, calcium aluminate cement, pyrope stone powder and alumina powder and additives and bridging agent B as fine powder.
[0050] In the present invention, a bridging agent A is added to the raw material of the working surface, and a bridging agent B is added to the raw material of the backing surface. Bridging agent A is one or more of sodium carbonate, sodium silicate, potassium carbonate, and potassium silicate; bridging agent B is sodium disilicate and / or phosphorus pentoxide. Both bridging agent A and bridging agent B are raw materials that react at relatively low temperatures to generate a glass phase. Bridging agent A forms a glass phase on the working surface, forming an integral structure with other raw materials, and bridging agent A plays the role of a connecting framework. Bridging agent B forms a glass phase in the backing surface, forming an integral structure with other raw materials, and bridging agent B plays the role of a connecting framework. At the interface between the working surface and the backing surface, bridging agent A and bridging agent B react to form a stable structure; at the same time, the products of bridging agent A and bridging agent B respectively form an integral structure with the working surface through bridging agent A, and form an integral structure with the backing surface through bridging agent B; thereby playing the role of connecting and fixing the working surface and the backing surface, thereby avoiding the separation of the working surface and the backing surface, and ensuring the integrated structure of the entire prefabricated brick. In addition, when the prepared composite refractory prefabricated bricks are made into a furnace for the production of artificial synthetic mica, at about 1000°C, bridging agent A and bridging agent B undergo a chemical reaction to generate a low-melting-point phase, which is stably retained. During use, the low-melting substance produces a liquid phase in the matrix, thereby eliminating thermal stress and expansion stress, and further avoiding the separation of the working surface and the backing surface.
[0051] In the present invention, the composite refractory precast bricks prepared by the action of bridging agent A and bridging agent B are of an integrated structure. When the furnace prepared by using the composite refractory precast bricks is used for the production of artificial synthetic mica, the entire composite refractory precast bricks will not separate or fall off.
[0052] In the present invention, the inventors have found through experiments that adding a bridging agent A to the raw material of the working surface and a bridging agent B to the raw material of the backing surface can effectively connect the working surface and the backing surface, so that the working surface and the backing surface are an integral structure.
[0053] Furthermore, the inventors have found through experiments that the amount of bridging agent A and bridging agent B also affects the bonding strength between the working surface and the backing surface. If the amount of bridging agent A and bridging agent B is too little, the bonding strength between the working surface and the backing surface will be relatively small. If the amount of bridging agent A and bridging agent B is too large, there will be too many reaction products of bridging agent A and bridging agent B at the interface between the working surface and the backing surface, which will also affect the bonding strength between the working surface and the backing surface. At the same time, the amount of bridging agent A and bridging agent B also affects the compressive strength of the entire precast brick. The appropriate amount of bridging agent A and bridging agent B plays a bonding role, which is beneficial to improve the compressive strength of the precast brick; however, when the amount of bridging agent A and bridging agent B is excessive, it will affect the mutual bonding of other components in the working surface and the backing surface, thereby affecting the compressive strength. Therefore, the reasonable control of the dosage of bridging agent A and bridging agent B can further improve the performance of the precast bricks and further ensure the performance of the furnace made of the composite refractory precast bricks.
[0054] Preferably, the bonding strength and compressive strength of the working surface and the backing surface of the composite refractory precast brick are balanced, and the amount of bridging agent A is selected to be 0.01-1wt% of the total amount of other raw materials on the working surface, preferably 0.05-0.8wt%, and more preferably 0.1-0.5wt%; the amount of bridging agent B is 0.01-1wt% of the total amount of other raw materials on the backing surface, preferably 0.05-0.8wt%, and more preferably 0.1-0.5wt%. It can not only ensure the bonding strength of the working surface and the backing surface in the composite refractory precast brick, but also make the compressive strength of the entire composite refractory precast brick meet the requirements of making an artificial synthetic mica furnace, thereby ensuring the reuse rate of the entire furnace and increasing the service life of the furnace.
[0055] In the present invention, the raw materials used in the working surface are all high temperature resistant and corrosion resistant inorganic substances, and the thickener acts as a binder to thicken the raw materials. Zirconia corundum powder, white corundum powder, and alumina powder are all commercially available products.
[0056] In the present invention, the raw materials used in the working surface are all inorganic substances with good heat resistance and thermal insulation performance, and the additives serve as binders to play the role of bonding the raw materials. White corundum powder, coke stone powder, alumina powder, and calcium aluminate cement are all commercially available products.
[0057] Preferably, in order to improve the strength of the backing surface, raw materials with different particle sizes are selected and combined among the aggregate raw materials of the backing surface, so as to ensure the strength of the backing surface.
[0058] In the present invention, the thickness of the working surface and the thickness of the backing surface are not limited. Generally, the thickness of the working surface is 5-50 mm, and the thickness of the backing surface is 100-500 mm.
[0059] In the present invention, the composite refractory prefabricated bricks are made of specific raw materials and specific dosages, and the preparation method is relatively conventional. The composite refractory prefabricated bricks can be obtained through ordinary mixing, drying and roasting.
[0060] In the present invention, the mixing time is generally 3-30 minutes, preferably 5-20 minutes. Drying can be carried out by air drying or by using a dryer at 30-100°C, and the calcination temperature is generally 600-1500°C.
[0061] Compared with the prior art, the technical solution provided by the present invention has the following beneficial technical effects: 1. The present invention utilizes the characteristics of two different refractory materials, the backing surface and the working surface, to make the prefabricated block for synthetic mica furnace have slight or no erosion by mica products and thermal insulation performance, thus solving the problem of adhesion between artificial synthetic mica furnace products and clay bricks; 2. In order to solve the stress cracking between the double-layer interface, the present invention introduces bridging agent A and bridging agent B into the two layers of materials respectively. Bridging agent A and bridging agent B play the role of connecting and fixing the working surface and the backing surface; at the same time, bridging agent A and bridging agent B play the role of skeleton and connection in the entire prefabricated brick.
[0062] 3. The composite refractory prefabricated bricks prepared by the present invention are of an integrated structure, which reduces the erosion of the synthetic mica on the refractory lining material and avoids the problem of the refractory lining material being corroded and contaminating the mica product during the smelting process; 4. The composite refractory prefabricated bricks prepared by the present invention have the function of being reused, thus avoiding waste of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 The present invention is a schematic structural diagram of a composite refractory prefabricated brick for an artificial synthetic mica furnace. DETAILED DESCRIPTION
[0064] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.
[0065] A composite refractory prefabricated brick for an artificial synthetic mica melting furnace, the composite refractory prefabricated brick comprising a working surface and a backing surface; characterized in that: the raw material of the working surface is composed of one or more of zirconium corundum powder, white corundum powder, and alumina powder, a thickener, and a bridging agent A; the raw material of the backing surface is composed of coke powder and / or high-alumina bauxite powder as aggregate, and one or more of white corundum powder, calcium aluminate cement, coke powder, and alumina powder, an additive, and a bridging agent B as fine powder; Wherein: bridging agent A is one or more of sodium carbonate, sodium silicate, potassium carbonate and potassium silicate; bridging agent B is sodium disilicate and / or phosphorus pentoxide.
[0066] Preferably, in the working surface raw materials, the amount of bridging agent A is 0.01-1wt%, preferably 0.05-0.8wt%, and more preferably 0.1-0.5wt% of the total amount of other raw materials of the working surface.
[0067] Preferably, in the raw materials of the backing surface, the amount of the bridging agent B is 0.01-1 wt %, preferably 0.05-0.8 wt %, and more preferably 0.1-0.5 wt % of the total amount of other raw materials of the backing surface.
[0068] Preparation process: A method for artificially synthesizing composite refractory prefabricated bricks for mica melting furnaces, the method comprising the following steps: (1) Preparation of backing surface mud: add the backing surface fine powder raw material according to the proportion, stir for 15 minutes, mix evenly, and obtain matrix fine powder; then stir the backing surface aggregate for 5 minutes to mix evenly, add the matrix fine powder, and then add 5% water (based on the weight of the powder raw material), stir for 10 minutes to obtain backing surface mud; (2) Preparation of working surface mud: Add the working surface raw materials according to proportion, stir for 20 minutes, mix evenly, add 18% water (based on the weight of the powder raw materials), continue stirring for 10 minutes, and obtain the working surface mud; (3) Preparation of composite refractory precast bricks for artificial synthetic mica melting furnace: first pour the backing surface clay into the mold and vibrate to form it. After the backing surface clay is vibrated to level it, pour the working surface clay into the mold and vibrate to form it. After vibrating to level it, dry it at room temperature for 2 hours, then roast it at 900℃ for 12 hours, and cool it to obtain composite refractory precast bricks for artificial synthetic mica melting furnace.
[0069] The thickness of the working surface of the composite refractory prefabricated brick is 10 mm, and the thickness of the backing surface is 230 mm.
[0070] The above-mentioned preparation method was used to adjust the raw material composition and component dosage of the refractory precast bricks, and the following experiments were carried out respectively: Example 1
[0071] The raw materials of the working surface mud are: 8Kg of zirconium corundum fine powder, 1Kg of white corundum fine powder, 1Kg of alumina powder, 0.05Kg of hydroxymethyl cellulose, and 0.02Kg of Na2SiO3; Backing surface mud raw material composition: Matrix subdivision: white corundum fine powder 1.0Kg, pyrochlorephthalate fine powder 1.2Kg, activated alumina powder 0.5Kg, pure calcium aluminate cement 0.5Kg, silica fume 0.3Kg, P2O5 0.02Kg.
[0072] Aggregates: high alumina clinker (5-3mm) 2Kg, coke stone (3-2mm) 1.5Kg, coke stone (2-1mm) 1.5Kg, coke stone (1-0.5mm) 2Kg. Example 2
[0073] The raw materials of the working surface mud are: 8Kg of zirconium corundum fine powder, 1Kg of white corundum fine powder, 1Kg of alumina powder, 0.03Kg of polyacrylamide, and 0.02Kg of sodium carbonate; Backing surface mud raw material composition: Matrix subdivision: 1.0Kg white corundum fine powder, 1.2Kg pyrochlorephthalate fine powder, 0.5Kg activated alumina powder, 0.5Kg pure calcium aluminate cement, 0.3Kg sodium tripolyphosphate, 0.02Kg sodium disilicate.
[0074] Aggregate: 2Kg of pyroxene (5-3mm), 1.5Kg of pyroxene (3-2mm), 1.5Kg of pyroxene (2-1mm), 2Kg of pyroxene (1-0.5mm). Example 3
[0075] The raw materials of the working surface mud are composed of 8 kg of zirconium corundum fine powder, 1 kg of white corundum fine powder, 1 kg of alumina powder, 0.03 kg of polyacrylamide, and 0.02 kg of sodium silicate; Backing surface mud raw material composition: Matrix subdivision: 1.0Kg of white corundum fine powder, 1.2Kg of pyroxene fine powder, 0.5Kg of activated alumina powder, 0.5Kg of pure calcium aluminate cement, 0.3Kg of sodium hexametaphosphate, and 0.02Kg of sodium disilicate.
[0076] Aggregates: high alumina clinker (5-3mm) 2Kg, high alumina clinker (3-2mm) 1.5Kg, high alumina clinker (2-1mm) 1.5Kg, high alumina clinker (1-0.5mm) 2Kg. Example 4
[0077] Example 1 was repeated, except that the bridging agent A was sodium carbonate. Example 5
[0078] Example 1 was repeated, except that the bridging agent A was potassium carbonate. Example 6
[0079] Example 1 was repeated, except that the bridging agent A was potassium silicate. Example 7
[0080] Example 1 was repeated, except that the added amounts of Na2SiO3 and P2O5 were both 0.0005 kg. Example 8
[0081] Example 1 was repeated, except that the added amounts of Na2SiO3 and P2O5 were both 0.005 kg. Example 9
[0082] Example 1 was repeated, except that the added amounts of Na2SiO3 and P2O5 were both 0.1 kg. Example 10
[0083] Example 1 was repeated, except that the added amounts of Na2SiO3 and P2O5 were both 0.5 kg.
[0084] Comparative Example 1 Working surface mud raw materials: 8Kg zirconium corundum fine powder, 1Kg white corundum fine powder, 1Kg alumina powder, 0.05Kg hydroxymethyl cellulose; Backing surface mud raw material composition: Matrix subdivision: 1.0Kg white corundum fine powder, 1.2Kg pyroxene fine powder, 0.5Kg activated alumina powder, 0.5Kg pure calcium aluminate cement, 0.3Kg silica fume.
[0085] Aggregates: high alumina clinker (5-3mm) 2Kg, coke stone (3-2mm) 1.5Kg, coke stone (2-1mm) 1.5Kg, coke stone (1-0.5mm) 2Kg.
[0086] The refractory prefabricated bricks prepared in Examples 1-10 and Comparative Example 1 were cut into 160 mm long * 40 mm wide * 40 mm thick (including a 10 mm working surface and a 30 mm backing surface) samples using a special brick cutting machine. The national standard GB / T3001-2017 refractory material room temperature flexural strength test method was used to test the adhesion between the working surface and the backing surface. The national standard GB / T5072-2008 refractory material room temperature compressive strength test method was used to test the compressive strength of the samples. The test results are shown in the following table:
[0087] The refractory prefabricated bricks prepared in Examples 1 to 10 were built into a furnace with a diameter of 2.5 to 3.4 meters (variable diameter); the furnace was used to produce synthetic mica, and the impurity content in the synthetic mica products was detected by spectral analysis (GB / T 21114), and the impurity rate was less than 1‰. Among them, the furnace made of the refractory prefabricated bricks prepared in Example 1 was used to produce synthetic mica, and the impurity content in the synthetic mica products was detected, and the impurity rate was only 0.3 per ten thousand.
[0088] Among the raw materials used in the embodiments of the present invention, the inorganic raw materials only need to meet the requirements of their particle size and composition. Among them: Zirconia corundum fine powder: particle size ≤0.076mm, Al2O3 content of 68%, ZrO2 content of 26%, SiO2 content of 5%. White corundum fine powder: particle size ≤0.076mm, Al2O3 of 99.5%. Alumina micropowder (activated alumina powder): Al2O3 is 99.8%, particle size is 0.5-10μm. Pyrope fine powder: Al2O3 content is 44%, Fe2O3 is 1.2%. Pure calcium aluminate cement: Al2O3 content is 78%. High alumina clinker: Al2O3 content is 68%, 5-3mm. All inorganic materials are commercially available products.
[0089] The hydroxymethylcellulose was 419273 produced by Merck KGaA, Germany, with an average Mw of 90,000. The polyacrylamide was 749222 produced by Merck KGaA, Germany, with an average Mn of 150,000. The sodium tripolyphosphate was 238503 produced by Merck KGaA, Germany, with an analytical quantity of 36786. The sodium hexametaphosphate was 71600 produced by Merck KGaA, Germany, with a concentration of 65-70% P2O5.
Claims
1. A composite refractory prefabricated brick for an artificial synthetic mica melting furnace, the composite refractory prefabricated brick comprising a working surface and a backing surface; characterized in that: The working surface raw material is composed of one or more of zirconium corundum powder, white corundum powder, alumina powder, thickener, and bridging agent A; the backing surface raw material is composed of coke powder and / or high-alumina bauxite powder as aggregate, and one or more of white corundum powder, calcium aluminate cement, coke powder and alumina powder, additives, and bridging agent B as fine powder; Wherein: bridging agent A is one or more of sodium carbonate, sodium silicate, potassium carbonate and potassium silicate; bridging agent B is sodium disilicate and / or phosphorus pentoxide.
2. The composite refractory prefabricated brick for artificial synthetic mica melting furnace according to claim 1 is characterized in that: In the working surface raw materials, the amount of bridging agent A is 0.01-1wt% of the total amount of other raw materials of the working surface, preferably 0.05-0.8wt%, more preferably 0.1-0.5wt%; In the backing surface raw materials, the amount of bridging agent B used is 0.01-1wt% of the total amount of other raw materials of the backing surface, preferably 0.05-0.8wt%, and more preferably 0.1-0.5wt%.
3. The composite refractory prefabricated brick for artificial synthetic mica furnace according to claim 2 is characterized in that: The raw material composition of the working surface is: 70-90 parts by weight of zirconium corundum powder, preferably 72-88 parts by weight, more preferably 74-86 parts by weight; 2-30 parts by weight, preferably 4-25 parts by weight, more preferably 6-20 parts by weight of white corundum powder; 2-30 parts by weight of alumina powder, preferably 4-25 parts by weight, more preferably 6-20 parts by weight; Thickener 0.1-2 parts by weight, preferably 0.15-1.5 parts by weight, more preferably 0.2-1 parts by weight; The bridging agent A is 0.01-1 part by weight, preferably 0.05-0.8 part by weight, and more preferably 0.1-0.5 part by weight.
4. The composite refractory prefabricated brick for artificial synthetic mica furnace according to claim 2 is characterized in that: The raw materials of the backing surface include aggregate raw materials and fine powder raw materials; Wherein: the amount of aggregate raw materials is 50-90% of the total amount of the backing surface raw materials, preferably 55-85%, more preferably 60-80%; The raw material composition of fine powder is: 2-25 parts by weight, preferably 4-20 parts by weight, more preferably 6-15 parts by weight of white corundum powder; 5-25 parts by weight of coke gemstone powder, preferably 7-20 parts by weight, more preferably 10-15 parts by weight; 1-10 parts by weight of alumina powder, preferably 2-9 parts by weight, more preferably 3-8 parts by weight; 1-10 parts by weight of calcium aluminate cement, preferably 2-9 parts by weight, more preferably 3-8 parts by weight; 0.5-10 parts by weight of additives, preferably 1-8 parts by weight, more preferably 2-5 parts by weight; The bridging agent B is 0.01-1 part by weight, preferably 0.05-0.8 part by weight, and more preferably 0.1-0.5 part by weight.
5. The composite refractory prefabricated brick for artificial synthetic mica furnace according to any one of claims 1 to 4, characterized in that: The particle size of the zirconium corundum powder is ≤0.076 mm, the Al2O3 content is ≥65%, the ZrO2 content is ≥20%, and the SiO2 content is ≤15%; The particle size of the white corundum powder is ≤0.076 mm, and the Al2O3 content is ≥99%; The aluminum oxide powder contains Al2O3≥99 and a particle size of 0.5-10 μm; The high-alumina bauxite contains Al2O3≥65%; The Al2O3 content in the coke gemstone powder is 30-50%, and the Fe2O3 is ≤2%.
6. The composite refractory prefabricated brick for artificial synthetic mica furnace according to any one of claims 1 to 4, characterized in that: The thickener is hydroxymethyl cellulose or polyacrylamide; and / or The additive is one or more of silica fume, sodium tripolyphosphate or sodium hexametaphosphate.
7. The composite refractory prefabricated brick for artificial synthetic mica melting furnace according to any one of claims 1 to 4, characterized in that: In the backing surface aggregate raw materials, the pyrope powder is composed of pyrope powder of various particle sizes; and / or the high-alumina bauxite powder is composed of high-alumina bauxite powder of various particle sizes; Preferably, the backing surface aggregate raw materials include raw materials with particle sizes of 0.5-1mm, 1-2mm, 2-3mm, and 3-5mm; preferably, the raw materials with a particle size of 0.5-1mm account for 20-30%, the raw materials with a particle size of 1-2mm account for 15-25%, the raw materials with a particle size of 2-3mm account for 15-25%, and the raw materials with a particle size of 3-5mm account for 20-30%.
8. The composite refractory prefabricated brick for artificial synthetic mica melting furnace according to any one of claims 1 to 7, characterized in that: The calcium aluminate cement is pure calcium aluminate cement, with Al2O3 72-82%, CaO 19-23%; and / or The alumina powder is activated alumina powder.
9. The composite refractory prefabricated brick for artificial synthetic mica furnace according to any one of claims 1 to 8, characterized in that: The thickness of the working surface is 5-50 mm, preferably 8-30 mm; and / or The thickness of the backing surface is 100-500 mm, preferably 150-400 mm.
10. A method for preparing the composite refractory prefabricated brick for artificial synthetic mica furnace according to any one of claims 1 to 9, the method comprising the following steps: (1) Preparation of backing surface mud: add the backing surface fine powder raw material in proportion and mix evenly to obtain matrix fine powder; then mix the backing surface aggregate evenly, add the matrix fine powder, and then add 1-10% of water and mix to obtain backing surface mud; (2) Preparation of working surface mud: Add the working surface raw materials according to proportion, mix evenly, add 15-25% of water, continue stirring, and obtain the working surface mud; (3) Preparation of composite refractory precast bricks for artificial synthetic mica melting furnace: first, pour the backing surface mud into the mold and vibrate to form it. After the backing surface mud is vibrated to level it, pour the working surface mud into the mold and vibrate to form it. After vibrating and solidifying, the composite refractory precast bricks for artificial synthetic mica melting furnace are obtained.
Citation Information
Patent Citations
Lightweight sound, heat and fire insulating material - contg. expanded mica, hydraulic binders and silicate additive
CH581084A5
Chromium corundum structure heat-insulation integrated composite brick and preparation method thereof
CN102230739A
A zirconia-corundum integrated thermal insulation composite brick and its preparation method
CN102261846A
Low-heat-conduction fused cast zirconia-corundum compound bricks and production method thereof
CN102538468A
Composite refractory brick containing floating beads
CN105503222A
